SON 50 YILDA DOĞU ANADOLU FAY HATTI ÜZERİNDE MEYDANA GELEN YIKICI DEPREMLER SONUCUNDA OLUŞAN HASARIN İNCELENMESİ - ÖZ, GÜLLÜ (Fırat Üniveristesi, 2022)
Türkiye tektonik olarak aktif bir bölgede olduğundan sık sık depremler meydana gelmektedir. Tektonik karakter, esas olarak Avrasya Plakası ile Arap Plakası arasında devam eden çarpışmadan kaynaklanmaktadır. Ülkenin çoğu, Kuzey Anadolu Fay Sistemi (KAF) ve Doğu Anadolu Fay Sistemi (DAFS) olarak adlandırılan iki ana doğrultu atımlı fay kuşağı ile sınırlanan Anadolu Plakası üzerinde yer almaktadır. Bu fay sistemlerinden Doğu Anadolu fay sistemi tarih boyunca birçok yıkıcı depremle karşı karşıya kalmış ve bu nedenle bölge birçok araştırmaya konu olmuştur. Meydana gelen yıkıcı depremler bölgede maddi ve manevi birçok hasara neden olmuştur. Depremler bölgenin gelişmesi önünde büyük engeller yaratarak önlem alınması gerektiğini bize önemle hatırlatmıştır. Bölge 1971 Bingöl, 1976 Çaldıran, 1998 Adana, 2003 Bingöl, 2010 Kovancılar. 2011 Van ve son olarak 2020 Sivrice depremleri ile sarsılmıştır. Bu depremler birçok maddi ve manevi hasara neden olmuştur. Bu depremler sonucu oluşan hasarların bilinmesi oluşabilecek kayıpların önüne geçilebilmesi açısından önemlidir. Anahtar Kelimeler: Doğu Anadolu fay sistemi, yapısal hasar, deprem

Since Turkey is in a tectonically active region, earthquakes occur frequently. The tectonic character is mainly due to the ongoing collision between the Eurasian Plate and the Arabian Plate. Most of the country lies on the Anatolian Plate, which is bounded by two main strike-slip fault zones called the North Anatolian Fault System (NAF) and the East Anatolian Fault System (EAFS). One of these fault systems, the Eastern Anatolian fault system has faced many destructive earthquakes throughout history and therefore the region has been the subject of many studies. The devastating earthquakes that occurred have caused many material and moral damages in the region. Earthquakes have created great obstacles to the development of the region and reminded us that precautions should be taken. The region was shaken by the 1971 Bingöl, 1976 Çaldıran, 1998 Adana, 2003 Bingöl, 2010 Kovancılar. 2011 Van and finally 2020 Sivrice earthquakes. These earthquakes caused many material and moral damages. Knowing the damages caused by these earthquakes is important in order to prevent possible losses. Keywords: Eastern Anatolian fault system, structural damage, earthquake
Investigation of damage caused by destructive earthquakes on the Eastern Anatolian fault line in the last 50 years
Keywords: İnşaat Mühendisliği